Studi Kinetika Adsorpsi : Pemanfaatan Limbah Biji Pepaya (Carica papaya L.) sebagai Adsorben Ion Logam Cd(II) dan Pb(II) Pada Limbah Dengan Metode Batch - Ilham, Rachmannu; Rahmah, Fatati K; Said, Nurul F; Rofianto, Erfan (LPPM, Institut Teknologi Sepuluh Nopember, 2023)
Currently, papaya seed waste (Carica papaya L.) is very abundant and easy to obtain because papaya is included in the fruit group whose harvest season is throughout the year. Papaya seeds are also included in a sustainable energy source. This research aims to study the adsorption kinetics of papaya seed adsorbents on Cd(II) and Pb(II) metal ions in laboratory waste. Several innovations were made including variations in adsorbent mass, contact time and pH. Optimum absorption efficiency of Cd(II) metal occurs with an adsorbent weight of 4 grams, equilibrium time of 90 minutes and pH 7. Papaya seed adsorbent is able to absorb Cd(II) metal ions up to 0.138 mg/g with a maximum absorption of 103.66%. Whereas for Pb(II) metal occurs at the optimum condition of adsorbent weight of 1 gram, equilibrium time of 60 minutes and pH 6. These conditions are able to adsorb up to 1.037 mg/g with absorption efficiency reaching 91.31%. The results of processing the kinetic data showed that the adsorption kinetics of Cd(II) followed the Pseudo Second Order model with an initial absorption rate of 0.1710 mg/g min. Whereas for metal Pb(II) follows the Elovich model with an initial adsorption rate of 0.045 mg/g min and a covered surface area of 2.8993 (g/mg). The implementation of waste was able to adsorb 0.122 mg/g of Cd(II) metal ions with 79.42% absorption and 0.993 mg/g of Pb(II) metal ions with 99.60% absorption.